Next Generation Sequencing in Non-Small Cell Lung Cancer: Pitfalls and Opportunities - Chiara Lazzari; Alessandra Bulotta; Maria Giulia Cangi; Gabriele Bucci; Lorenza Pecciarini; Silvia Bonfiglio; Vincenza Lorusso; Stefania Ippati; Gianluigi Arrigoni; Greta Grassini; Claudio Doglioni; Vanesa Gregorc (Diagnostics, 2020)
Lung cancer remains the first cause of cancer-related deaths worldwide. Thanks to the improvement in the knowledge of the biology of non-small cell lung cancer (NSCLC), patients’ survival has significantly improved. A growing number of targetable molecular alterations have been identified. Next-generation sequencing (NGS) has become one of the methodologies entered in clinical practice and was recently recommended by the European society for medical oncology (ESMO) to perform a comprehensive molecular characterization in patients with cancer. The current review provides an overview of the clinical trials that have explored the impact of NGS in patients with cancer, its limits, and advantages.